Effect of therapeutic exercise on peak oxygen consumption in oncological population: a systematic review with meta-analysis - Del Rosal Jurado, Alicia; González-Sánchez, Manuel; Cuesta-Vargas, Antonio (Springer, 2024)
Cancer is amongst the leading causes of death worldwide. A total of 19.3 million new cases were diagnosed in 2020. Cardiovascular impairment is the second leading cause of death in patients undergoing cancer treatment. By measuring the maximum rate of oxygen consumption (VO2max) in cancer patients, it is possible to estimate their cardiorespiratory health. This study aims to show how participants’ VO2max increases with a therapeutic physical exercise programme.
Keywords: Enfermedad cardiovascular; Fisioterapia; Cancer; Neoplasms; Exercise Respiratory function tests; Cardiorespiratory fitness